Catheter ablation in patients with atrial fibrillation and heart failure with preserved ejection fraction: A systematic review and meta‐analysis. Issue 6 (29th October 2022) - Siddiqui, Muhammad U.; Junarta, Joey; Riley, Joshua M.; Ahmed, Adnan; Pasha, Ahmed K.; Limbrick, Kolin; Alvarez, Rene J.; Frisch, Daniel R.
Abstract: Background: Catheter ablation for atrial fibrillation (AF) is a proven alternative to pharmacologic rhythm control in patients with heart failure with reduced ejection fraction (HFrEF). Whether outcomes differ in patients with heart failure with preserved ejection fraction (HFpEF) is of interest. Methods: Medline, Scopus, and Cochrane Central Register of Controlled Trials were systematically searched to identify relevant studies. Primary efficacy outcomes of interest include atrial arrythmia recurrence and repeat ablation. Harm outcomes of interest include all‐cause mortality, all‐cause hospitalizations, cardiovascular hospitalizations, stroke/transient ischemic attack, and cardiac tamponade. Results: We included 7 observational studies comprising 2554 patients with HFpEF who underwent catheter ablation for AF. When comparing patients with HFpEF versus without HF, there was no significant difference in atrial arrhythmia recurrence (risk ratio [RR] 1.39; 95% confidence interval [CI] 0.91–2.13), stroke or transient ischemic attack (TIA) (RR 0.47; 95% CI 0.03–6.54), or cardiac tamponade (RR 1.20; 95% CI 0.12–12.20). When comparing patients with HFpEF versus HFrEF, there was no significant difference in atrial arrhythmia recurrence (RR 1.12; 95% CI 0.92–1.37), repeat ablation (RR 1.19; 95% CI 0.74–1.93), all‐cause mortality (RR 0.87; 95% CI 0.67–1.13), all‐cause hospitalizations (RR 1.10; 95% CI 0.94–1.30), cardiovascular hospitalizations (RR 0.83; 95% CI 0.69–1.01), stroke or TIA (RR 0.81; 95% CI 0.29–2.25), or cardiac tamponade (RR 0.98; 95% CI 0.19–5.16). Conclusions: Non‐randomized studies suggest that catheter ablation for AF in patients with HFpEF is associated with similar arrythmia‐free survival and safety profile when compared to patients with HFrEF or without heart failure. Abstract : Non‐randomized studies suggest that catheter ablation for AF in patients with HFpEF is associated with similar arrythmia free survival and safety profile when compared to patients with HFrEF and without heart failure. Ultimately, this suggests that patients with AF and HFpEF may benefit equally as those with AF and HFrEF.